2021
DOI: 10.3389/fenrg.2021.683166
|View full text |Cite
|
Sign up to set email alerts
|

How Does Industrial Structure Upgrading Affect the Global Greenhouse Effect? Evidence From RCEP and Non-RCEP Countries

Abstract: This study empirically investigates the impact of industrial structure upgrading on global carbon dioxide (CO2) emissions by employing a balanced dataset of 73 countries over the period 1990–2019. After conducting a series of empirical tests, we used the fixed effect (FE) and random effect (RE) methods to estimate the econometric model, and divided the full sample data into two subsamples, i.e., Regional Comprehensive Economic Partnership (RCEP) countries and non-RCEP countries, for heterogeneous analysis. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…On the other hand, high-level human capital with good environmental awareness [ 50 ] will increase the consumption proportion of environmentally friendly, green, and low-pollution consumer goods that are conducive to green growth. In addition, consumption structure upgrade will also force the production sector to improve and iterate products [ 6 , 49 , 51 ], which is conducive to producing more environmentally friendly products [ 52 ]. Therefore, human capital at this stage will positively promote green economy development.…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
“…On the other hand, high-level human capital with good environmental awareness [ 50 ] will increase the consumption proportion of environmentally friendly, green, and low-pollution consumer goods that are conducive to green growth. In addition, consumption structure upgrade will also force the production sector to improve and iterate products [ 6 , 49 , 51 ], which is conducive to producing more environmentally friendly products [ 52 ]. Therefore, human capital at this stage will positively promote green economy development.…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
“…Rapid economic expansion is grounded in the early stages by huge energy consumption, which would be accompanied by large volumes of environmental pollution. However, once economic growth reaches a particular level, environmental regulation trends to become more stringent, taking into account the greenhouse effect's implications [72].…”
Section: Long-run and Short-run Elasticitiesmentioning
confidence: 99%
“…Khan et al found that industrial growth contributed to the long-term rise in CO 2 emissions in seven South Asian countries [ 57 ]. Dong et al found that for both Regional Comprehensive Economic Partnership (RECP) countries and non-RECP countries, the upgrading of industrial structure would help reduce CO 2 emissions [ 58 ]. Liu et al have shown that secondary industry is the main source of CO 2 emissions in Beijing.…”
Section: Industrial Transfer and Co 2 Emissions: Literature Review And Analysis Frameworkmentioning
confidence: 99%